Gatekeepers to Justice: Police Officers’ Experiences Responding to Sexual Assault - Murphy-Oikonen, Jodie (Crime & delinquency, 2024)
Police officers play a central role in attaining justice for sexual assault survivors. Disclosing sexual assault is critical to attain justice and foster support, yet survivors often experience negative interactions when disclosing sexual victimization to the police. Police officers’ experiences investigating sexual assault have not been explored. Qualitative methods were used to explore the experiences of police officers who respond to reports of sexual assault. Semi-structured interviews with 20 police officers were analyzed in NVIVO software and uncovered four themes, (1) Lack of Sexual Assault Training; (2) Compassion for the Victim; (3) Investigative Process, and (4) Police Distress. The first-hand accounts of police officers uncover opportunities to improve police response to sexual assault and enhance the disclosure experience of survivors.